2006
DOI: 10.1210/me.2005-0010
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Glucose Transporter 9 Splice Variants Are Expressed in Adult Liver and Kidney and Are Up-Regulated in Diabetes

Abstract: A novel glucose transporter (GLUT), mouse GLUT9 (mGLUT9), was recently cloned from mouse 7-d embryonic cDNA. Several splice variants of mGLUT9 were described, two of which were cloned (mGLUT9a and mGLUT9a Delta 209-316). This study describes the cloning and characterization of another splice variant, mGLUT9b. Cloned from adult liver, mGLUT9b is identical to mGLUT9a except at the amino terminus. Based on analysis of the genomic structure, the different amino termini result from alternative transcriptional/trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
92
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(102 citation statements)
references
References 24 publications
5
92
1
1
Order By: Relevance
“…Thus, Glut9 may be involved in both steps of transepithelial urate transport, mostly in the distal tubule. We also confirmed that Glut9 is expressed at the plasma membrane of all hepatocytes (20) (Fig. S2).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Thus, Glut9 may be involved in both steps of transepithelial urate transport, mostly in the distal tubule. We also confirmed that Glut9 is expressed at the plasma membrane of all hepatocytes (20) (Fig. S2).…”
Section: Resultssupporting
confidence: 79%
“…The long form is targeted to the basolateral membrane and the short form to the apical membrane of polarized epithelial cells (19,20). In the human kidney, Glut9 is present in proximal convoluted tubules, whereas in rodents it is most probably in distal connecting tubules (20). Functional studies confirmed that Glut9 is a urate transporter (18,21) and mutations in its sequence cause hypouricemia in human subjects (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…GLUT9 has the structure of a type II Glut isoform, with 12 transmembrane domains, a large extracellular loop between the first and second transmembrane domains, and both amino- and carboxyterminal ends on the cytoplasmic side (82). In both humans and mice, GLUT9 exists as two alternatively spliced variants that encode different aminoterminal cytoplasmic tails (83,84). Human GLUT9a has 540 amino acids and is encoded by 12 exons, whereas GLUT9b is 512 amino acids long and encoded by 13 exons, spread over an approximately 250-kb genomic region.…”
Section: Other Genes Identified By Genetic Association Studiesmentioning
confidence: 99%
“…In polarized epithelial cells, human GLUT9a is expressed in the basolateral membrane, whereas GLUT9b is targeted to the apical pole (84), and in human kidney, GLUT9 is present in the proximal tubule (84). In the mouse, Glut9 is present in the distal convoluted tubule (83), both in the basolateral and apical membranes (87) (Figure 3), but it is not yet known which isoform is present in each pole of the cells, in particular since both mouse isoforms have been reported to be targeted to the basolateral membrane of MDCK cells (83).…”
Section: Other Genes Identified By Genetic Association Studiesmentioning
confidence: 99%